Shape analysis applied in heavy ion reactions near Fermi energy. (2nd February 2017) - Zhang, S; Huang, M; Wada, R; Liu, X; Lin, W; Wang, J
Abstract: A new method is proposed to perform shape analyses and to evaluate their validity in heavy ion collisions near the Fermi energy. In order to avoid erroneous values of shape parameters in the calculation, a test particle method is utilized in which each nucleon is represented by n test particles, similar to that used in the Boltzmann–Uehling–Uhlenbeck (BUU) calculations. The method is applied to the events simulated by an antisymmetrized molecular dynamics model. The geometrical shape of fragments is reasonably extracted when n  = 100 is used. A significant deformation is observed for all fragments created in the multifragmentation process. The method is also applied to the shape of the momentum distribution for event classification. In the momentum case, the errors in the eigenvalue calculation become much smaller than those of the geometrical shape analysis and the results become similar between those with and without the test particle method, indicating that in intermediate heavy ion collisions the shape analysis of momentum distribution can be used for the event classification without the test particle method.